Launching ADVANCE care planning as a collabrative approach. Issue 1 (1st June 2011) - Fowler, C; Bettany, A; White, J; Finch, J
Abstract : A multi-organisational/professional project group formed to implement advance care planning, to include the Preferred Priorities of Care document. An early outcome indicated the need to develop a communication pathway and engage with the out of hours providers. Consequently the group developed the use of The Lions 'Message in a Bottle' (MIB), a plastic bottle placed in a patients fridge to hold key information about an individual's ACP and contact numbers of health professionals involved with the patient. The purpose of the MIB was to ensure patients wishes and preferences were known, and to assist the Out of Hours GPs and Ambulance service in difficult decision making. The project identified other areas to address to ensure the implementation of advance care planning was robust; ▶ EoLC Education to Emergency Care Practitioners, (ambulance professionals with a remit to prevent admission). ▶ Advance care planning workshops for all health and social care professionals. ▶ A succinct transfer of information form ▶ Collaborative End of Life Care registers between in hours and out of hours. The project is being launched to an audience of 80 encompassing commissioners, GPs, user representation, Acute and Community staff, care home staff, Learning Disability and Mental Health nurses, Hospital Consultants, Adult Care Services, Hospice staff and many others. The impact of the launch will be measured using a confidence questionnaire. The longer term outcomes for commissioners will include; ▶ Increased home deaths ▶ Fewer hospital admissions. These will be monitored using vital signs data.